Flavouring group evaluation 420 (FGE.420): Hesperetin dihydrochalcone - EFSA Panel on Food Additives and Flavourings (FAF); Laurence Castle; Monica Andreassen; Gabriele Aquilina; Maria Bastos; Polly Boon; Biagio Fallico; Reginald FitzGerald; Maria Jose Frutos Fernandez; Bettina Grasl‐Kraupp; Ursula Gundert‐Remy; Rainer Gürtler; et al. (EFSA Journal)
Abstract The EFSA Panel on Food Additives and Flavourings (FAF) was requested to evaluate the safety of hesperetin dihydrochalcone [FL‐no: 16.137] as a new flavouring substance, in accordance with Regulation (EC) No 1331/2008. The substance is structurally related to the group of flavonoids evaluated in FGE.32 and is the aglycone of neohesperidine dihydrochalcone. Based on the data provided for [FL‐no: 16.137], the Panel considered that a read‐across between hesperetin dihydrochalcone and the substances in FGE.32 is not needed. Nevertheless, the flavonoids evaluated in FGE.32 were considered in a cumulative exposure assessment. The information provided on the manufacturing process, the composition and the stability of [FL‐no: 16.137] was considered sufficient. The Panel concluded that there is no concern with respect to genotoxicity. No absorption, distribution, metabolism and excretion (ADME) studies on [FL‐no: 16.137] were provided, but studies investigating the ADME of neohesperidine dihydrochalcone were submitted. The Panel noted that [FL‐no: 16.137] has the same fate in the organism, as that of neohesperidine dihydrochalcone and considered that [FL‐no: 16.137] can be anticipated to be metabolised to innocuous products only. In a prenatal developmental toxicity study, no maternal or foetal toxicity was observed. In a 90‐day toxicity study, indications were obtained that the substance affects thyroid hormone levels at all doses tested (100–1000 mg/kg bw per day). Since these changes were not accompanied by apical findings indicative of hypothyroidism, the Panel considered these hormonal effects as not adverse. Using 1000 mg/kg bodyweight (bw) per day as reference point, adequate margins of exposure were calculated for adults and children, when considering the chronic added portions exposure technique (APET) dietary exposure estimates. Cumulative chronic exposure estimates to [FL‐no: 16.137] and the four structurally related substances evaluated in FGE.32 do not raise a safety concern. The use of [FL‐no: 16.137] as food flavouring, under the proposed conditions of use, does not raise a safety concern.